2021
DOI: 10.3389/fpls.2021.650926
|View full text |Cite
|
Sign up to set email alerts
|

From “Dark Matter” to “Star”: Insight Into the Regulation Mechanisms of Plant Functional Long Non-Coding RNAs

Abstract: Long non-coding RNAs (lncRNAs) play a vital role in a variety of biological functions in plant growth and development. In this study, we provided an overview of the molecular mechanisms of lncRNAs in interacting with other biomolecules with an emphasis on those lncRNAs validated only by low-throughput experiments. LncRNAs function through playing multiple roles, including sponger for sequestering RNA or DNA, guider or decoy for recruiting or hijacking transcription factors or peptides, and scaffold for binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 90 publications
(142 reference statements)
0
28
0
Order By: Relevance
“…In recent years, long non‐coding RNAs (lncRNAs) have been emerging as cryptic but important regulators of gene expression in various biological processes (Chen et al., 2021; Rinn & Chang, 2012). LncRNAs are generally defined as non‐protein‐coding RNA transcripts longer than 200 nucleotides (Guttman et al., 2013; Sun & Kraus, 2015), although a few studies have suggested some lncRNAs might also produce small polypeptides (Ruiz‐Orera et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, long non‐coding RNAs (lncRNAs) have been emerging as cryptic but important regulators of gene expression in various biological processes (Chen et al., 2021; Rinn & Chang, 2012). LncRNAs are generally defined as non‐protein‐coding RNA transcripts longer than 200 nucleotides (Guttman et al., 2013; Sun & Kraus, 2015), although a few studies have suggested some lncRNAs might also produce small polypeptides (Ruiz‐Orera et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Their functions yet remain largely unknown. However, more and more studies have shown that some LncRNAs play a vital role in some biological progress ( Chen et al, 2021 ). For instance, in Arabidopsis , several functional LncRNAs were identified and involved in cell phosphate homeostasis ( Shin et al, 2006 ); in strawberry, one LncRNA was identified to play a role in fruit ripening ( Tang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in Arabidopsis , several functional LncRNAs were identified and involved in cell phosphate homeostasis ( Shin et al, 2006 ); in strawberry, one LncRNA was identified to play a role in fruit ripening ( Tang et al, 2021 ). Functional LncRNAs were also detected in other plant species, for example, rice, maize, lemon, etc., ( Chen et al, 2021 ). In the Solanaceae family, functional LncRNAs were identified only in tomato ( Solanum Lycopersicum ) and relevant with disease resistance, hormone signal pathway, and nitrogen deficiency ( Cui et al, 2017 ; Wang et al, 2018 ; Jiang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a close regulatory relationship among lncRNAs, miRNAs, and mRNAs ( Voshall et al, 2017 ). In recent years, studies on lncRNA-miRNA-mRNA regulatory networks have revealed that lncRNAs, as a type of competing endogenous RNA (ceRNA), competitively bind the same miRNA as mRNAs, which reduces the probability of miRNA-mRNA binding and increases the expression of mRNAs ( Chen et al, 2021 ). To date, many lncRNAs involved in the nitrogen deficiency response have been identified in model plants ( Chen et al, 2016 ; Fukuda et al, 2019 , 2020 ; Liu et al, 2019 ; Lu et al, 2019 ; Wang et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%